“Lawless Coal Miners” and the Lingan Strike of 1882–1883: Remaking Political Order on Cape Breton’s Sydney Coalfield - Nerbas, Don (Labour / Le Travail)

(untitled) (Canadian Committee on Labour History, 2023)
The Lingan strike of 1882–83 was the last in a series of strikes over a two-decade period on Cape Breton Island’s Sydney coalfield. With the use of untapped local sources, this article reconstructs the history of this understudied strike within a broader history of social relations on the coalfield. The migration of labourers from the island’s backland farms – predominantly from Highland enclave settlements – to the coal mines played a decisive role in shaping the era’s new coal mining villages and the character of social conflict. By the early 1880s, structural change associated with National Policy industrialism was eroding the old authority of the coal operators, and miners embraced the Provincial Workmen’s Association (pwa) to advance their claims in long-standing and highly localized contestations. Ultimately the coal communities themselves imposed the emergent trade unionism. The Lingan strike marked a transition to a new political order on the coalfield, structured by the place of the coal mines within the wider Cape Breton countryside and built upon a powerful localism and moral economy that recast the public sphere and the miners’ place in it.